Overview of Environmental Jurisprudence within Environmental Ethics - Emina, Kemi Anthony (Universitas Negeri Makassar, 2020)
Environmental Jurisprudence’s highest achievement is its codification of a change in ethics, and a legal recognition that both individual and governmental agency responsibility extend to the natural world. This article provides an overview of Environmental Jurisprudence as it relates to environmental ethics. It examines both the foundation of Environmental Jurisprudence as well as the concept of human rights. The article also critically discusses international environmental law from the perspective of human rights. This research concludes by arguing that despite the attempt made in the international regime for adding eco-centric values in environmental law, environmental jurisprudence to date has continued with anthropocentric ideas with all concerns for safeguarding the means of human survival.